Diagnostic accuracy of saline infusion sonography as compared to hysteroscopy in premenopausal women with abnormal uterine bleeding - Tangri, Manoj Kumar; Srivastava, Ajay Krishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: In patients with abnormal uterine bleeding (AUB), differentiating whether the cause is anovulation or anatomic lesions can be challenging. Transvaginal sonography (TVS) has limitation in form of high false negative rate for diagnosing focal intrauterine pathology. To improve the image in TVS, saline injected into uterine cavity can be used as a negative contrast agent. Aim of our study was to evaluate the clinical value of saline infusion sonography (SIS) by comparing its diagnostic accuracy with that of established gold standard i.e. hysteroscopy. Methods: The study was carried out in a referral and teaching public sector hospital in eastern India from July 2015 to June 2016. Study population consisted of 136 premenopausal women with AUB, who were scheduled to undergo diagnostic hysteroscopy. Patients were first evaluated by sis and then followed by hysteroscopy on a later date. Results: Both SIS and hysteroscopy could be successfully performed in 136 out of 144 patients. When all findings by SIS (any pathological findings in uterine cavity vs. none) were combined and compared with hysteroscopy (gold standard), both sensitivity and specificity of sis were 0.88 whereas PPV and NPV were 0.85 and 0.90 respectively. Conclusions: Because of comparable results obtained by evaluating patients by SIS as well as office hysteroscopy, we recommend saline infusion sonography as a valuable tool for evaluating premenopausal women with abnormal uterine bleeding, before consideration for hysteroscopy.